2021
DOI: 10.15251/cl.2021.182.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on the Structure and Optical Properties of Lead Selenide and Cadmium Selenide Thin Film Prepared by Chemical Bath Deposition

Abstract: The effect of annealing on the structural and optical properties of lead selenide and cadmium selenide thin films prepared by chemical bath deposition has been studied. The films were annealed in air for a duration of 1 hour at temperatures of 673 K for CdSe and 573 K for PbSe. Both the as-deposited and annealed films were characterized by X-ray diffraction and optical absorption spectroscopy. The as–deposited CdSe films had the cubic structure with preferred orientation along (111) plane. However, after annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The procedure used for the electrodeposition of lead tin sulphide (PbSnS) thin films is described in Nkrumah et al [14]. In this section we present a brief summary of this procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure used for the electrodeposition of lead tin sulphide (PbSnS) thin films is described in Nkrumah et al [14]. In this section we present a brief summary of this procedure.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous publication by Nkrumah et al [14], we reported on the electrodeposition of single-phase lead tin sulphide (PbSnS) thin films on ITO-coated glass substrates. In this paper, we investigated the type of majority charge carrier, optical and structural properties,…”
Section: Introductionmentioning
confidence: 99%
“…The energy band gap and type of electron transition were determined by the Stern relationship [27,28] which is given by the expression:…”
Section: Determination Of the Optical Band Gapmentioning
confidence: 99%
“…Calculation of the average grain size from the most intense peak was done using the Scherrer [23,24] formula which is given as;…”
Section: Average Grain Sizementioning
confidence: 99%